1999
DOI: 10.1074/jbc.274.18.12877
|View full text |Cite
|
Sign up to set email alerts
|

A Mammalian Lysosomal Membrane Protein Confers Multidrug Resistance upon Expression in Saccharomyces cerevisiae

Abstract: Mouse transporter protein (MTP) is a highly conserved polytopic membrane protein present in mammalian lysosomes and endosomes. The role of MTP in regulating the in vivo subcellular distribution of numerous structurally distinct small molecules has been examined in this study by its expression in a drug-sensitive strain of the yeast Saccharomyces cerevisiae. Surprisingly, the expression of MTP in membranes of an intracellular compartment resulted in a cellular resistance or hypersensitivity to a range of drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 61 publications
3
32
0
Order By: Relevance
“…Here, we report a novel interaction between MCOLN1 and the members of the LAPTM family. Although the cellular function of LAPTMs is not well understood, it has been suggested that LAPTMs might participate in the transport of small molecules across intracellular membranes (Hogue et al, 1996;Hogue et al, 1999). We found that MCOLN1 and LAPTMs colocalize to late endosomes and lysosomes and confirmed the interaction by coimmunoprecipitation in human cells.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Here, we report a novel interaction between MCOLN1 and the members of the LAPTM family. Although the cellular function of LAPTMs is not well understood, it has been suggested that LAPTMs might participate in the transport of small molecules across intracellular membranes (Hogue et al, 1996;Hogue et al, 1999). We found that MCOLN1 and LAPTMs colocalize to late endosomes and lysosomes and confirmed the interaction by coimmunoprecipitation in human cells.…”
Section: Introductionsupporting
confidence: 76%
“…Both clones were in-frame with the N-terminal half of ubiquitin. The function of LAPTMs is not completely understood but it has been suggested that they are transporters involved in the subcellular compartmentalization of different compounds (Hogue et al, 1996;Hogue et al, 1999). MCOLN1 protein binding to LAPTMs was confirmed by performing additional yeast twohybrid experiments.…”
Section: Identification Of Laptms As Novel Mcoln1 Binding Partnersmentioning
confidence: 94%
“…LAPTM4 was shown previously to transport and sequestrate various small molecules, including nucleosides and antibiotics, into the lysosome, thereby protecting the cell from their harmful effects (5,12,13). This finding suggests that LAPTM5 may also function as an intracellular transporter to the lysosome.…”
Section: Discussionmentioning
confidence: 76%
“…LAPTM5 contains five membrane-spanning segments, three polyproline-tyrosine motifs, and a ubiquitin-interacting motif at its C terminus (33). LAPTM4, structurally related to LAPTM5, was shown previously to transport and sequestrate various small molecules, including nucleosides and antibiotics, into the lysosome, thereby protecting the cell from their harmful effects (5,12,13). Even though the exact function of LAPTM5 remains ill defined, recent studies demonstrated that LAPTM5 is involved in the regulation of antigen receptor expression on the surface of lymphocytes after antigen stimulation (31,32).…”
mentioning
confidence: 99%
“…However, there is no ATP binding sites in the molecular structure of LAPTM4B from bioinformatics analysis. Therefore, it might be less possibility that LAPTM4B-35 itself is a kind of multidrug transporter, despite LAPTM4A is thought to function as a transporter protein (Cabrita et al, 1999;Hogue et al, 1999). Another mechanism for MDR involves in alterations in the apoptotic response associated with PI3K/AKT signaling.…”
Section: Discussionmentioning
confidence: 99%